(untitled) (International Journal of Contemporary Security Studies, 2024)
The security situation at the global level worsened especially at the end of the 20th and the beginning of the 21st century.Terrorism has become one of the biggest threats today.The targets became: physical and technical objects, infrastructure objects, communications of strategic importance, various state and international systems of vital importance for the functioning of states and the international community, and of course human lives.In addition to the measurable damage to these facilities and systems, terrorism also causes great fear and horror because of its terrifying brachial physical methods.Fear and terror grip all layers of society, from children to representatives of the highest executive authorities.Such fear leads to changes in the official policies of states and international organizations. In this paper, we will analyze crisis situations resolved by engaging special police units.By collecting, analyzing, interpreting and presenting quantitative and qualitative data that determine the basic elements of a crisis situation, that is, by looking at crisis situations through a scientific statistical method, we will gain insight into the ability and effectiveness of the police in combating terrorism.This approach will allow drawing conclusions about the factors that determine the operability of police special units.We will also be able to conclude what needs to be done in order to maintain such operability at the required level.